Synthesis and biological evaluation of 9-N-oxamyl sialosides as Siglec-7 ligands. Issue 17 (1st September 2015) - Prescher, Horst; Gütgemann, Stephan; Frank, Martin; Kuhfeldt, Elena; Watzl, Carsten; Brossmer, Reinhard
Graphical abstract: Abstract: Siglecs (sialic acid recognizing immunoglobulin like lectins) are a family of lectins with specificity for sialic acid containing carbohydrates. Synthetic sialic acid derivatives with high affinity proved useful to unravel the biological role of the ligand binding domain, although many of their functions in immunity remain unknown. Here we present design, synthesis, affinity evaluation and molecular modeling of novel 9- N -oxamoyl modified sialosides as Siglec-7 ligands.